2018
DOI: 10.1136/jim-2017-000546
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Carotenoid Measurement is Inversely Related to Anxiety in Patients with Breast Cancer

Abstract: Breast cancer is the most prevalent malignancy among women worldwide. Increased oxidative stress and poor subjective health outcomes have been associated with increased risk of cancer recurrence and metastasis, but few studies until now have explored the relationship between oxidative stress and chronic stress/anxiety. This study aims to examine the association between anxiety and a potential dermal correlate of oxidative stress in patients with breast cancer. 102 breast cancer patients were enrolled in a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The ROC curve reflected that the disease progression events could be effectively distinguished with the SAS_A score, which was consistent with the conclusions drawn from previous studies. 9 In this study, area under the ROC curve (AUC) = 0.8306, Std.Error = 0.02353, 95% confidence interval (CI) = 0.7845 to 0.8767, a p-value of <0.0001, cut-off = 53.5, sensitivity = 66.67% (57.20% to 74.95%), and specificity = 86.51% (83.66% to 88.93%). As distinguished by the SAS_A cut-off value based on the KM analysis, it was found that there was a difference between the group with relatively high SAS_A scores and that with relatively low SAS_A scores, a p-value of <0.0001, the median of no events: SAS_Low: Un; SAS_High: 22 months; HR (high–low): 4.085 (2.582–6.462).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The ROC curve reflected that the disease progression events could be effectively distinguished with the SAS_A score, which was consistent with the conclusions drawn from previous studies. 9 In this study, area under the ROC curve (AUC) = 0.8306, Std.Error = 0.02353, 95% confidence interval (CI) = 0.7845 to 0.8767, a p-value of <0.0001, cut-off = 53.5, sensitivity = 66.67% (57.20% to 74.95%), and specificity = 86.51% (83.66% to 88.93%). As distinguished by the SAS_A cut-off value based on the KM analysis, it was found that there was a difference between the group with relatively high SAS_A scores and that with relatively low SAS_A scores, a p-value of <0.0001, the median of no events: SAS_Low: Un; SAS_High: 22 months; HR (high–low): 4.085 (2.582–6.462).…”
Section: Resultsmentioning
confidence: 77%
“… 8 Due to the complication of negative emotions, the mortality risk of patients with breast cancer is increased by 19%. 9 Group psychological intervention is conducive to the psychological adjustment of patients with breast cancer. 10 Conventional nursing models usually provide conventional psychological interventions for patients with breast cancer which have given initial results, but the overall effect is not ideal.…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot study of 20 patients that were suffering from various cancers, it was shown that the concentration of carotenoids in the SC of patients that were measured before chemotherapy was significantly lower than that of healthy individuals ( p < 0.001) [ 219 ], probably due to the psychological burden and anxiety that cancer patients suffered from or the accumulating long-lasting effect of previous chemotherapy cycles [ 220 ]. Although the concentration of carotenoids in the SC does not correlate with the age of a healthy person [ 192 ], such a correlation has been found for the skin of patients suffering from cancer, which was decreasing with increasing patient age [ 221 ].…”
Section: Factors Resulting In the Reduction Of Carotenoids In The Scmentioning
confidence: 99%
“…[33][34][35][36][37][38] Furthermore, it can be stated that cancer subjects already show significantly lower SERRDS carotenoid intensities before chemotherapy treatment compared to healthy subjects. This can be due to the cancerous disease itself and associated emotional burden and stress, [39][40][41] due to co-medication or even to prior chemotherapeutical treatments at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%